A brief history of tendon and ligament bioreactors: Impact and future prospects. Issue 11 (1st July 2020) - Dyment, Nathaniel A.; Barrett, Jennifer G.; Awad, Hani A.; Bautista, Catherine A.; Banes, Albert J.; Butler, David L.
Abstract: Bioreactors are powerful tools with the potential to model tissue development and disease in vitro. For nearly four decades, bioreactors have been used to create tendon and ligament tissue‐engineered constructs in order to define basic mechanisms of cell function, extracellular matrix deposition, tissue organization, injury, and tissue remodeling. This review provides a historical perspective of tendon and ligament bioreactors and their contributions to this advancing field. First, we demonstrate the need for bioreactors to improve understanding of tendon and ligament function and dysfunction. Next, we detail the history and evolution of bioreactor development and design from simple stretching of explants to fabrication and stimulation of two‐ and three‐dimensional constructs. Then, we demonstrate how research using tendon and ligament bioreactors has led to pivotal basic science and tissue‐engineering discoveries. Finally, we provide guidance for new basic, applied, and clinical research utilizing these valuable systems, recognizing that fundamental knowledge of cell‐cell and cell‐matrix interactions combined with appropriate mechanical and chemical stimulation of constructs could ultimately lead to functional tendon and ligament repairs in the coming decades.